Growth of NIH 3T3 Fibroblast Cells Exposed to Carbonated Hydroxyapatite with Incorporated Propolis - Wijayanti, Puspaneka; Lastianny, Sri Pramestri; Suryono, Suryono (Indonesian Society for Cancer Chemoprevention, 2020)
Carbonated hydroxyapatite is frequently used as bone graft material in dentistry. It is highly biocompatible, has osteoconductive properties, and functions as a drug delivery system. Propolis is a natural product from bees that has antibacterial and anti-inflammatory effects and is capable of accelerating wound healing. Incorporating propolis into carbonated hydroxyapatite was expected to enhance the wound-healing process by stimulating fibroblast growth and regenerating alveolar bone in the treatment of periodontitis. The aim of this study was to evaluate the effect of carbonated hydroxyapatite with incorporated propolis on the viability of NIH 3T3 fibroblast cells. This study used three treatment groups [carbonated hydroxyapatite with various concentrations of incorporated propolis (5%, 7.5%, and 10%)] and one control group (carbonated hydroxyapatite with no propolis). An MTT assay was carried out to assess cell viability, and absorbance readings were performed by using an ELISA reader. The data were analyzed by using one-way ANOVA. The results showed significant differences between all groups, and carbonated hydroxyapatite with 10% incorporated propolis has the highest cell viability level of all groups, while the control group has the lowest cell viability. In conclusion, adding propolis to carbonated hydroxyapatite could increase the growth of NIH 3T3 fibroblast cells. Keywords: Carbonated hydroxyapatite, Propolis, NIH 3T3 fibroblast cells, MTT assay